Employer Branding : Employer Attractiveness, Corporate Reputation, and Job Application Intentions - Larsson, Stefan; Rosell, Hanna (2014)
The competition for attracting the most talented people is increasing. Employer branding is a concept that concerns both the marketing and human resource functions of organizations. In order to attract the desired employees, companies benefit from understanding what it is that make an employer attractive. Only then, it is possible to create an efficient employer brand that attracts employees. The purpose if this thesis is to describe the factors of employer attractiveness that influence corporate reputation and intentions to pursue a job application. The nature of this research is exploratory and explanatory. A quantitative study was conducted to answer the research purpose, where a questionnaire was sent to students of Luleå University of Technology. The results suggest that social value is the most important factor of employer attractiveness, followed by development value. Findings also suggest a relation between some factors of employer attractiveness and corporate reputation, which in turn is related to a potential employee’s intention to pursue a job application. Validerat; 20140708 (global_studentproject_submitter)